Critical Role of Somatosensation in Postural Control Following Spaceflight: Vestibularly Deficient Astronauts Are Not Able to Maintain Upright Stance During Compromised Somatosensation - Ozdemir, Recep A.; Goel, Rahul; Reschke, Millard F.; Wood, Scott J.; Paloski, William H. (Frontiers in Physiology, 2018)
The free-fall of orbital spaceflight effectively removes the gravitational vector used as a primary spatial orientation reference on Earth. Sustained absence of this reference drives adaptive changes in the internal perception-action models of the central nervous system (CNS), most notably in the processing of the vestibular otolith inputs. Upon landing, the return of the gravitational signal triggers a re-adaptation that restores terrestrial performance; however, during this period, the individual suffers from a functional vestibular deficiency. Here we provide evidence of a transient increase of the weighting of somatosensory inputs in postural control while the CNS resolves these vestibular deficiencies. Postural control performance was measured before and after spaceflight in 11 Shuttle astronauts and 11 matched controls and nine elderly who did not experience spaceflight. A quiet-stance paradigm was used that eliminated vision, modulated the lower extremity somatosensory cues by subtly modulating the orientation of the support surface beneath feet of subjects in all groups. Additionally, in astronauts and matched controls, we challenged the vestibular system with dynamic head tilts. Postural stability on the landing day (R+0) was substantially decreased for trials with absent visual and altered somatosensory cues, especially those also requiring dynamic head tilts (±5° @ 0.33 Hz) during which 20/22 trials ended prematurely with a fall. In contrast, none of the astronauts fell during eyes-closed, dynamic head tilt trials with unaltered somatosensory cues, and only 3/22 trials resulted in falls with eyes-closed and altered somatosensory cues, but static upright head orientation. Furthermore, postural control performance of astronauts was either statistically not different or worse than that of healthy elderly subjects during the most challenging vestibular conditions on R+0. Overall, our results demonstrate a transient reweighting of sensory cues associated with microgravity-induced vestibular deficiencies, with a significant increase in reliance on somatosensory cues, which can provide an effective reference even without vision and dynamic vestibular challenges. The translation of these results to aging population suggests that elderly individuals with visual and vestibular deficits may benefit from therapeutic interventions enhancing sensorimotor-integration to improve balance and reduce the risk of falling.